The Effect of Strategic Planning on Quality Control in The Iron and Steel Industry in Libya (American Journal of Economics and Business Innovation, 2023)
The present study aims to investigate the phenomenon under examination through a rigorous academic lens. The determinant of a company’s competitive edge and sustainability in the marketplace is primarily attributed to the factor of quality. Strategic planning plays a pivotal role in influencing quality control outcomes. Therefore, the objective of this study is to examine the influence of strategic planning on quality control within the Iron and Steel sector in developing nations. The study’s objectives were accomplished through the implementation of a quantitative methodology. During the data collection phase of this study, a sample of 384 employees employed at the Libyan Iron and Steel Company was obtained. The study employed Structural Equation Modeling (SEM) to assess the influence of strategic planning on quality control. The results of this study demonstrated a statistically significant and positive relationship between strategic planning and quality control. The present study provides practical implications, offers recommendations for future research directions, and acknowledges certain limitations.